Changes in temporomandibular joint anatomy, changes in condylar translation, and their relationship with disc displacement: magnetic resonance imaging study - Bedran,Luciane Marie (2019)
Abstract Objective: To assess changes in the articular surfaces of the temporomandibular joint (TMJ) and in condylar translation, as detected by magnetic resonance imaging (MRI), determining whether such changes correlate with disc displacement. Materials and Methods: We retrospectively analyzed the MRI scans of 2076 TMJs of 1038 patients with symptoms of temporomandibular disorder. We attempted to determine whether articular disc deformity and changes in condylar translation, as well as changes in the articular surfaces of the condyle, glenoid fossa, and articular eminence, correlated with disc displacement. Results: Disc displacement with reduction was associated with changes in the shape of the articular eminence. Disc displacement without reduction was most strongly associated with disc deformity, condylar degeneration, glenoid fossa degeneration, and effusion. Neither decreases nor increases in condylar translation were associated with disc deformity, degenerative bone changes, or disc displacement. Conclusion: Changes in the shape of the articular eminence seem to predispose to progression of internal derangement of the TMJ.